ChemInform Abstract: Synthesis of Novel 5‐Oxaprotoberberines as Bioisosteres of Protoberberines. Issue 31 (5th August 2014) - Jin, Yifeng; Khadka, Daulat Bikram; Yang, Su Hui; Zhao, Chao; Cho, Won‐Jea
Abstract The synthesis of 5‐oxaprotoberberines involves the coupling of toluamides (I) with 2‐cyanophenol derivatives and SN2 reaction with diiodomethane to form the methylene bridge between amide and hydroxyl group.